Analisis Faktor Yang Mempengaruhi Kinerja Penelitian Dosen Perguruan Tinggi Swasta (Pts) Kluster Madya Di Kota Malang - Lukitaningtias, Firina; Hernanik, Nova Dwi (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
ABSTRACT. Lecturers are one of the important components in Higher Education. The roles, duties and responsibilities of lecturers become an important matter in the role of contributing to the realization of the National Education Goals. One component is the involvement of lecturers in implementing the Tridharma of Higher Education as a form of lecturer performance. The Tridharma includes education and teaching, research, and community service. This study aims to analyze the factors that influence the performance of private university (PTS) middle class lecturers in Malang City, especially in the field of research, which has not received much attention. The research method used is explanatory research with a quantitative approach. Data collection techniques were carried out using a questionnaire distributed to 40 PTS lecturers in the middle cluster in Malang City. Data analysis techniques using multiple regression analysis. The results showed that the variables of ability and expertise (X1), motivation (X2), organizational resources (X3), leadership (X4), and organizational structure (X5) simultaneously affected the research performance of PTS lecturers in the middle cluster in Malang. Keywords: Ability And Expertise, Motivation, Organizational Resources, Leadership, Organizational Structure, Lecturer Research Performance